Cross-talk connections underlying dorsal and ventral stream integration during hand actions. (June 2018) - Budisavljevic, Sanja; Dell'Acqua, Flavio; Castiello, Umberto
Abstract: According to the dual-stream theory, the processing of visual information is divided into a ventral pathway mediating object recognition, and a dorsal pathway supporting visuomotor control. Increasing evidence suggests that these streams are not independent, but where this dorsal-ventral stream integration occurs remains unknown. We explored the candidate white matter pathways linking dorsal and ventral visual streams in 30 right-handed participants performing object-oriented hand movements of varying complexity (reaching, grasping and lifting), using advanced diffusion imaging tractography based on the spherical deconvolution and kinematical analysis. We provided for the first time a direct evidence of cross-communication between dorsal and ventral visual streams in humans, through vertical occipital fasciculus and temporo-parietal fibers of the arcuate fasciculus during on-line control of grasping and lifting actions. We showed that individual differences in the microstructure of these cross-talk connections were associated with the variability of the arm deceleration, the grip opening and the grasp accuracy. This study suggests that hand kinematics, in skilled hand actions where high degree of online control is required, is related to the anatomy of the cross-talk networks between dorsal and ventral streams, bringing important insights to the dual-stream theory and the sensorimotor organization of hand actions.